Geodynamic Setting and Cu-Ni Potential of Late Permian Xiwanggou Mafic-Ultramafic Rocks, East Kunlun Orogenic Belt, NW China - Zhang, Jiandong; Yu, Miao; Wang, Hui; Li, Bin; Feng, Chengyou; Dick, J. M.; Li, Jinchao; Kong, Huilei; Zhao, Zhiyi (Frontiers in Earth Science, 2021)
Several magmatic Cu–Ni sulfide deposits have recently been explored along the deep Middle Kunlun fault related to the extension of the East Kunlun orogenic belt in Qinghai Province, NW China. The Xiwanggou mafic–ultramafic rocks associated with Cu–Ni sulfide mineralization are first to be dated as late Permian compared to most of the deposits formed during late Silurian–early Devonian in this region. The Xiwanggou complexes located in the junction area between the East Kunlun and West Qinling belts, are composed of gabbros, olivine-gabbros, pyroxenites, olivine-pyroxenites, and peridotites. The Cu–Ni mineralization are mainly hosted in the olivine-pyroxenites and pyroxenites, whereas the sulfide-poor mineralization distributed in gabbros and olivine-gabbros. Zircon LA-ICP-MS U–Pb dating of the gabbro and olivine-pyroxenite revealed their crystallized ages of 250.8 ± 0.8 Ma and 257.3 ± 0.7 Ma, respectively. The trace element characteristics of the Xiwanggou fertile mafic-ultramafic rocks shows the enrichments in Sr, Rb, Th, Ba and light rare earth elements, and depletions in Nb and Ta, which are associated with the slab derived fluid input and dehydration melting of amphiboles. Meanwhile, Sr–Nd and Hf isotopic compositions of the gabbro [εNd(t) = 0.66–1.18; εHf(t) = 5.2–12] and olivine-pyroxenite [εNd(t) = −1.09 – −0.43; εHf(t) = 5.4–17.7] show that the magma was mainly derived from the metasomatized portions of subcontinental lithospheric mantle (SCLM) source in the mantle wedge. The magma primarily experienced dehydration melting processes of amphiboles and subsequently underwent hydrated melting in the overlying mantle wedge and relatively reduced background. The cool subduction process of the Anemaqen oceanic lithosphere maybe trigger large melting in the mantle wedge resulting in a relative low-Ni content in the melt. The transpressional windows formed by the right-lateral strike-slip shearing action of the Wenquan and South Kunlun faults in the South Kunlun forearc belt created a significant conduit for the magma ascending. The thermometer of Fe and Ni exchange between coexisting olivine and sulfide melt indicates the magma were yielded in a temperature range of ca. 1200–1300°C and an oxygen fugacity range of ca. –10.57 to –8.98 (log unit), which suggested that the parental magma of the Xiwanggou complex derived from a relatively reduced source favoring Ni relative to Fe in the melt. The intermediate sulfide segregation from the melt resulted in a medium tenor potential for the Xiwanggou complex.